Comparison of glomerular filtration rate estimating equations derived from creatinine and cystatin C: validation in the Age, Gene/Environment Susceptibility-Reykjavik elderly cohort. Issue 8 (5th October 2017) - Björk, Jonas; Grubb, Anders; Gudnason, Vilmundur; Indridason, Olafur S; Levey, Andrew S; Palsson, Runolfur; Nyman, Ulf
Abstract: Background: Validation studies comparing glomerular filtration rate (GFR) equations based on standardized creatinine and cystatin C assays in the elderly are needed. The Icelandic Age, Gene/Environment Susceptibility-Kidney cohort was used to compare two pairs of recently developed GFR equations, the revised Lund–Malmö creatinine equation (LMRCr ) and the arithmetic mean of the LMRCr and Caucasian, Asian, Paediatric and Adult cystatin C equations (MEANLMR+CAPA ), as well as the Full Age Spectrum creatinine equation (FASCr ) and its combination with cystatin C (FASCr+Cys ), with the corresponding pair of Chronic Kidney Disease Epidemiology Collaboration equations (CKD-EPICr and CKD-EPICr+Cys ). Methods: A total of 805 individuals, 74–93 years of age, underwent measurement of GFR (mGFR) using plasma clearance of iohexol. Four metrics were used to compare the performance of the GFR equations: bias, precision, accuracy [including the percentage of participants with estimated GFR (eGFR) within 30% of mGFR (P30 )] and the ability to detect mGFR <60 mL/min/1.73 m 2 . Results: All equations had a P30  >90%. LMRCr and FASCr yielded significantly higher precision and P30 than CKD-EPICr, while bias was significantly worse. LMRCr, FASCr and CKD-EPICr showed similar ability to detect mGFR <60 mL/min/1.73 m 2 based on the area under the receiver operating characteristic curves. MEANLMR+CAPA, FASCr+Cys and CKD-EPICr+Cys all exhibited consistent improvements compared with the corresponding creatinine-based equations. Conclusion: None of the creatinine-based equations was clearly superior overall in this community-dwelling elderly cohort. The addition of cystatin C improved all of the creatinine-based equations.